2019
DOI: 10.1161/hypertensionaha.118.12305
|View full text |Cite
|
Sign up to set email alerts
|

Greater Blood Pressure Variability Is Associated With Lower Cognitive Performance

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…We recently showed both visit-to-visit and day-to-day BPV were related to clinical progression of Alzheimer's disease [42], although for visit-to-visit BPV this was not replicated in another dementia cohort [43]. In the Maastricht study, a composite score comprising 24h and day-to-day BPV was associated with cognitive performance [44]. The current study adds to the previous work on day-to-day BPV, by providing evidence for the potential underlying mechanism linking BPV and cognition.…”
Section: Discussionmentioning
confidence: 95%
“…We recently showed both visit-to-visit and day-to-day BPV were related to clinical progression of Alzheimer's disease [42], although for visit-to-visit BPV this was not replicated in another dementia cohort [43]. In the Maastricht study, a composite score comprising 24h and day-to-day BPV was associated with cognitive performance [44]. The current study adds to the previous work on day-to-day BPV, by providing evidence for the potential underlying mechanism linking BPV and cognition.…”
Section: Discussionmentioning
confidence: 95%
“…And no matter how baseline blood pressure was, higher systolic BPV, diastolic BPV, and mean arterial pressure variability were associated with poorer cognition and greater dementia risk. 43 Zhou et al 44 found that SBP and diastolic BPV have different influences on various cognitive domains. First, the larger DBP variability was associated with lower information processing speed and executive function, and significantly correlated with lower memory function.…”
Section: Influence Of Common Cvds On Cognitive Function In the Elderlymentioning
confidence: 99%
“…This educational classification is comparable with the International Standard Classification of Education (UNESCO, 2011), and results in a score between 1 and 7: (1) unfinished primary school, (2) finished primary school, (3) unfinished low-level secondary education, (4) lower vocational training, (5) advanced vocational training or lower professional education, (6) finished higher professional education or senior general secondary education, and (7) obtained a university degree (Verhage, 1964). Considering the low prevalence of individuals with unfinished primary school (n = 7) and a university degree (n = 31), we made the categorical distinction between low (Verhage scores 1-3), average (4-5), and high education level (6-7;Zhou et al, 2019).…”
Section: Educationmentioning
confidence: 99%